Developing a Strategic Leadership Approach within the Organizations - Marian NĂSTASE (Revista de Management Comparat International, 2010)
Business leaders are facing today a tough environment that force them to identify and implement innovative ways for managing their people and organization, in order to assure the survival and development of their organizations. Strategic leaders are concern with how to create and deliver the best value for their stakeholders, paying attention to their constraints. They understood that the traditional vertical chains of command are not longer enough and they have to be able to develop more horizontal networks, where there co-workers can learn, experiment and develop, both personally and professionally. This article deals with some challenges that the strategic leaders must take into account in developing competitive organizations, able to meet the new standards that are raised by a more dynamic and provoking business environment.